Demographics and survival of patients with idiopathic pulmonary fibrosis in the FinnishIPF registry - Jaana Kaunisto; Eija-Riitta Salomaa; Ulla Hodgson; Riitta Kaarteenaho; Hannu Kankaanranta; Katri Koli; Tero Vahlberg; Marjukka Myllärniemi (European Respiratory Society, 2022)
Idiopathic pulmonary fibrosis (IPF) is characterised by unpredictable disease course and poor survival. After the introduction of novel antifibrotic drugs, the prognosis of patients with IPF is probably changing.
FinnishIPF, a nationwide registry of carefully characterised patients, was initiated in Finland in 2011. For the data analysis, we included 453 incident IPF patients diagnosed during 2011–2015. In this study, we describe the demographics and prognosis of these real-life patients.
The median overall survival time of registered IPF patients was 4.5 years. The transplant-free survival at 1, 2, 3, 4 and 5 years was 95%, 83%, 70%, 58% and 45%, respectively. Smoking did not have any effect on survival. 117 (26%) patients received pirfenidone or nintedanib. Patients who received ≥6 months of treatment had better survival compared with those who did not receive treatment but this difference disappeared after age adjustment. The transplantation rate was 3%.
Although IPF is diagnosed in Finland at a older age, the prognosis is better than expected due to a relatively well preserved lung function at diagnosis. Age and pulmonary function were identified as independent predictors of survival in the entire IPF patient population as well as in patients who had received antifibrotic treatment.